Innovative Livelihood Restoration Program: Integrating Skills Development, Microfinance, and Local Market Opportunities - Neneng Nurbaeti Amien; N. Neni Triana; Imran Karo Karo (LPPM Institut Bisnis dan Informatika Kesatuan, 2026)
Livelihood restoration efforts in post-crisis contexts often rely on fragmented approaches, focusing separately on skills development, microfinance, or market access, which limits their effectiveness in achieving sustainable recovery. Despite their potential, there is still a lack of integrated models that examine how these components interact to strengthen long-term economic resilience among vulnerable populations. This study examines the integration of skills development, microfinance, and local market access as a comprehensive approach to livelihood restoration in post-crisis settings. Using a qualitative methodology, specifically a literature review, the study explores the role of these three components in fostering sustainable economic recovery. The data analysis indicates that when combined, these elements lead to a significant improvement in income generation, business growth, and employment outcomes. However, challenges such as market fragmentation, lack of coordination, digital adoption, and external socio-political factors are identified as barriers to success. The findings confirm that an integrated approach, which aligns skills development, microfinance, and market access, yields better results than individual interventions. The study emphasizes the need for context-specific, coordinated efforts to overcome barriers and ensure the long-term sustainability of livelihood restoration programs.